Early Psychoanalytic Religious Writings - Malony, H. Newton; Shafranske, Edward P. (Contemporary Psychoanalytic Studies, 2021)
Foreword -- 1 The Psychoanalytic Study of Religion: Past, Present, Future -- Edward Shafranske -- 2 Two Contributions to the Research on Symbols. ( Zwei Beitrage zur Symbolforschung . Imago IX, 1923, 122-126) -- A. Karl Abraham -- 3 If Moses was an Egyptian... ( Als Moses ein Agypter war . Imago XXIII, 1937, 387-419) -- Sigmund Freud -- 4 The Dogma of Christ. ( Die Entwicklung des Christusdogma . Imago XVI, 1930, 305-373) -- Erich Fromm -- 5 Two Traditions from Pascal's Childhood. ( Zwei Uberlieferungen aus Pascals Kinderjahren . Imago XI (3), 1935, 346-351) -- Imre Hermann -- 6 A Psychoanalytic Study of the Holy Spirit. ( Eine Psychoanalytischestudie uber den HeiligenGeist . Imago IX (1), 1923, 58-72) -- Ernest Jones -- 7 Is the Mark of Cain Circumcision? A Critical Contribution to Biblical Exegesis. ( Las das Kainnszeichen die Beshneidung . Imago V, 1919, 290-293) -- Lajos, Levy -- 8 The Illusion of the Future: A Friendly Dispute with Professor Sigmund Freud. ( Die Illusion einer Zukunft . Imago XIV, 1928, 149-184) -- Oskar Pfister -- 9 The Fifth Commandment. ( Das funfte Gebote . Imago IX, (1), 1923, 129-130) -- Sandor Rado -- 10 The Mark of Cain: A Psychoanalytic Contribution to Biblical Interpretation. ( Das Kainszaichen . Imago V, 1917, 31-42) -- Theodore Reik -- 11 Freud's Journal IMAGO - 1912 to Present -- 12 The Future of an Illusion: The Illusion of the Future: An Historic Dialogue on the Value of Religion. Between Oskar Pfister and Sigmund Freud (Reprinted with Permission from The Journal of the History of the Behavioral Sciences , 15(2), 1979, 177-186) -- H. Newton Malony and Gerald O. North -- Index.